Spatial Variations of Atmospheric Alkylated Polycyclic Aromatic Hydrocarbons across the Western Pacific to the Southern Ocean: Unexpected Increasing Deposition - Zhu, Fu-Jie; Lu, Xi-Mei; Jia, Jing-Wen; Zhang, Xue; Xing, De-Feng; Cai, Ming-Hong; Kallenborn, Roland; Li, Yi-Fan; Muir, Derek C. G.; Zhang, Zi-Feng; Zhang, Xianming (Environmental Science & Technology, 2025)
Spatial variations of atmospheric alkylated polycyclic aromatic hydrocarbons (Alk-PAHs) are key to understanding their long-range atmospheric transport (LRAT). However, limited Alk-PAHs data have hindered their LRAT characterizations on a global scale. In this study, 49 Alk-PAHs were measured in the atmospheric samples collected across the Western Pacific to the Southern Ocean. The summed concentration of 39 frequently detected Alk-PAHs (Σ39Alk-PAHs) was 25.8 ± 25.3 ng m–3. The concentrations of Σ39Alk-PAHs significantly declined with the decrease in latitude (°N). Higher concentrations (55.8 ± 33.8 ng m–3) were linked to continental air mass compared to oceanic/Antarctica air mass (17.0 ± 13.6 ng m–3), highlighting continental emissions as the primary source of marine atmospheric Alk-PAHs. An unexpected increase in the G/P partitioning ratio (KP) was found in samples farther away from the continent, which cannot be explained by the influence of temperature on the partitioning process. Deposition analysis suggested that gaseous concentrations and the G/P partitioning largely influenced deposition patterns. Hypothetical scenario analysis indicated that increased KP under snowy conditions could enhance the total Alk-PAH deposition. These findings emphasize the need for accurate characterization of partitioning and deposition processes when studying the global fate of Alk-PAHs, particularly in remote and polar regions.
Keywords: Sørishavet; atmosfæren; biokjemi; forurensning; kjemi; miljøgifter

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

Macronutrient biogeochemistry in Antarctic land-fast sea ice: Insights from a circumpolar data compilation - Henley, Sian F.; Cozzi, Stefano; Fripiat, François; Lannuzel, Delphine; Nomura, Daiki; Thomas, David N.; Meiners, Klaus M.; Vancoppenolle, Martin; Arrigo, Kevin; Stefels, Jacqueline; van Leeuwe, Maria; Moreau, Sebastien; et al. (Marine Chemistry, 2023)
Antarctic sea ice plays an important role in Southern Ocean biogeochemistry and mediating Earth's climate system. Yet our understanding of biogeochemical cycling in sea ice is limited by the availability of relevant data over sufficient temporal and spatial scales. Here we present a new publicly available compilation of macronutrient concentration data from Antarctic land-fast sea ice, covering the full seasonal cycle using datasets from around Antarctica, as well as a smaller dataset of macronutrient concentrations in adjacent seawater. We show a strong seasonal cycle whereby nutrient concentrations are high during autumn and winter, due to supply from underlying surface waters, and then are utilised in spring and summer by mixed ice algal communities consisting of diatoms and non-siliceous species. Our data indicate some degree of nutrient limitation of ice algal primary production, with silicon limitation likely being most prevalent, although uncertainties remain around the affinities of sea-ice algae for each nutrient. Remineralisation of organic matter and nutrient recycling drive substantial accumulations of inorganic nitrogen, phosphate and to a lesser extent silicic acid in some ice cores to concentrations far in excess of those in surface waters. Nutrient supply to fast ice is enhanced by brine convection, platelet ice accumulation and incorporation into the ice matrix, and under-ice tidal currents, whilst nutrient adsorption to sea-ice surfaces, formation of biofilms, and abiotic mineral precipitation and dissolution can also influence fast-ice nutrient cycling. Concentrations of nitrate, ammonium and silicic acid were generally higher in fast ice than reported for Antarctic pack ice, and this may support the typically observed higher algal biomass in fast-ice environments.
Keywords: Sørishavet; alger; havis; kjemi; marin biologi

Wind-driven upwelling of iron sustains dense blooms and food webs in the eastern Weddell Gyre - Moreau, Sebastien; Hattermann, Tore; de Steur, Laura; Kauko, Hanna M.; Ahonen, Heidi; Ardelan, Murat; Assmy, Philipp; Chierici, Melissa; Descamps, Sebastien; Dinter, Tilman; Falkenhaug, Tone; Fransson, Agneta; et al. (Nature Communications, 2023)
The Southern Ocean is a major sink of anthropogenic CO2 and an important foraging area for top trophic level consumers. However, iron limitation sets an upper limit to primary productivity. Here we report on a considerably dense late summer phytoplankton bloom spanning 9000 km2 in the open ocean of the eastern Weddell Gyre. Over its 2.5 months duration, the bloom accumulated up to 20 g C m−2 of organic matter, which is unusually high for Southern Ocean open waters. We show that, over 1997–2019, this open ocean bloom was likely driven by anomalies in easterly winds that push sea ice southwards and favor the upwelling of Warm Deep Water enriched in hydrothermal iron and, possibly, other iron sources. This recurring open ocean bloom likely facilitates enhanced carbon export and sustains high standing stocks of Antarctic krill, supporting feeding hot spots for marine birds and baleen whales.
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

Absence of photophysiological response to iron addition in autumn phytoplankton in the Antarctic sea-ice zone - Singh, A.; Fietz, S.; Thomalla, S. J.; Sanchez, N.; Ardelan, M. V.; Moreau, S.; Kauko, H. M.; Fransson, A.; Chierici, M.; Samanta, S.; Mtshali, T. N.; Roychoudhury, A. N.; et al. (Biogeosciences, 2023)
Keywords: Sørishavet; kjemi; marin biologi; oseanografi; plankton

New cold-adapted bacteria for efficient hydrolysis of feather waste at low temperature - Smirnova, Margarita; Losada, Cristian Bolaño; Akulava, Volha; Zimmermann, Boris; Kohler, Achim; Miamin, Uladzislau; Oostindjer, Marije; Shapaval, Volha (Bioresource Technology Reports, 2023)
A novel cold-adapted bacteria Arthrobacter oryzae BIM B-1663 isolated from Antarctic green snow showed keratinase activity and efficient poultry feather degradation. A. oryzae strain degraded more than 80 % of chicken feathers within 7 days of cultivation at 25 °C. The optimal keratinase activity for A. oryzae BIM B-1663 was observed at 50 °C, both for α-keratin (44.86 U/mL) and for β-keratin (94 mU/mL). The obtained results from sulfite and thiol groups tests and Fourier transform infrared spectroscopy (FTIR) showed that A. oryzae strain has a different keratin degradation mechanism than the reference strain Bacillus licheniformis CCM 2145T. FTIR fingerprinting can be used for monitoring of feather hydrolysis as it showed distinct chemical differences in feather meal hydrolysates, retentate and permeate from A. oryzae and B. licheniformis strains.
Keywords: Antarktis; bakterier; biokjemi; kjemi; mikrobiologi

The influence of energetic particle precipitation on Antarctic stratospheric chlorine and ozone over the 20th century - Maliniemi, V.; Arsenovic, P.; Seppälä, A.; Nesse Tyssøy, H. (Atmospheric Chemistry and Physics, 2022)
Keywords: Antarktis; kjemi; ozon; stratosfæren

Experimental warming increases fungal alpha diversity in an oligotrophic maritime Antarctic soil - Newsham, Kevin K.; Misiak, Marta; Goodall-Copestake, William P.; Dahl, Malin Stapnes; Boddy, Lynne; Hopkins, David W.; Davey, Marie L. (Frontiers in Microbiology, 2022)
The climate of maritime Antarctica has altered since the 1950s. However, the effects of increased temperature, precipitation and organic carbon and nitrogen availability on the fungal communities inhabiting the barren and oligotrophic fellfield soils that are widespread across the region are poorly understood. Here, we test how warming with open top chambers (OTCs), irrigation and the organic substrates glucose, glycine and tryptone soy broth (TSB) influence a fungal community inhabiting an oligotrophic maritime Antarctic fellfield soil. In contrast with studies in vegetated soils at lower latitudes, OTCs increased fungal community alpha diversity (Simpson’s index and evenness) by 102–142% in unamended soil after 5 years. Conversely, OTCs had few effects on diversity in substrate-amended soils, with their only main effects, in glycine-amended soils, being attributable to an abundance of Pseudogymnoascus. The substrates reduced alpha and beta diversity metrics by 18–63%, altered community composition and elevated soil fungal DNA concentrations by 1–2 orders of magnitude after 5 years. In glycine-amended soil, OTCs decreased DNA concentrations by 57% and increased the relative abundance of the yeast Vishniacozyma by 45-fold. The relative abundance of the yeast Gelidatrema declined by 78% in chambered soil and increased by 1.9-fold in irrigated soil. Fungal DNA concentrations were also halved by irrigation in TSB-amended soils. In support of regional- and continental-scale studies across climatic gradients, the observations indicate that soil fungal alpha diversity in maritime Antarctica will increase as the region warms, but suggest that the accumulation of organic carbon and nitrogen compounds in fellfield soils arising from expanding plant populations are likely, in time, to attenuate the positive effects of warming on diversity.
Keywords: Antarktis; kjemi; klimaendringer; mikrobiologi; sopper

First discrete iron(II) records from Dome C (Antarctica) and the Holtedahlfonna glacier (Svalbard) - Burgay, François; Barbaro, Elena; Cappelletti, David; Turetta, Clara; Gallet, Jean-Charles; Isaksson, Elisabeth; Stenni, Barbara; Dreossi, Giuliano; Scoto, Federico; Barbante, Carlo; Spolaor, Andrea (Chemosphere, 2021)
Fe(II) is more soluble and bioavailable than Fe(III) species, therefore the investigation of their relative abundance and redox processes is relevant to better assess the supply of bioavailable iron to the ocean and its impact on marine productivity. In this context, we present a discrete chemiluminescence-based method for the determination of Fe(II) in firn matrices. The method was applied on discrete samples from a snow pit collected at Dome C (DC, Antarctica) and on a shallow firn core from the Holtedahlfonna glacier (HDF, Svalbard), providing the first Fe(II) record from both Antarctica and Svalbard. The method showed low detection limits (0.006 ng g−1 for DC and 0.003 ng g−1 for the HDF) and a precision ranging from 3% to 20% RSD. Fe(II) concentrations ranged between the LoD and 0.077 ng g−1 and between the LoD and 0.300 ng g−1 for the Antarctic and Arctic samples, respectively. The Fe(II) contribution with respect to the total dissolved Fe was comparable in both sites accounting, on average, for 5% and 3%, respectively. We found that Fe(II) correctly identified the Pinatubo/Cerro Hudson eruption in the DC record, demonstrating its reliability as volcanic tracer, while, on the HDF core, we provided the first preliminary insight on the processes that might influence Fe speciation in firn matrices (i.e. organic ligands and pH influences).
Keywords: Antarktis; glasiologi; kjemi; polarområdene

Variability of Sea-Air Carbon Dioxide Flux in Autumn Across the Weddell Gyre and Offshore Dronning Maud Land in the Southern Ocean - Ogundare, Margaret Ojone; Fransson, Agneta; Chierici, Melissa; Joubert, Warren R.; Roychoudhury, Alakendra N. (Frontiers in Marine Science, 2021)
Sea surface fugacity of carbon dioxide (fCO2ssw) was measured across the Weddell gyre and the eastern sector in the Atlantic Southern Ocean in autumn. During the occupation between February and April 2019, the region of the study transect was a potential ocean CO2 sink. A net CO2 flux (FCO2) of −6.2 (± 8; sink) mmol m–2 d–1 was estimated for the entire study region, with the largest average CO2 sink of −10.0 (± 8) mmol m–2 d–1 in the partly ice-covered Astrid Ridge (AR) region near the coast at 68°S and −6.1 (± 8) mmol m–2d–1 was observed in the Maud Rise (MR) region. A CO2 sink was also observed south of 66°S in the Weddell Sea (WS). To assess the main drivers describing the variability of fCO2ssw, a correlation model using fCO2 and oxygen saturation was considered. Spatial distributions of the fCO2 saturation/O2 saturation correlations, described relative to the surface water properties of the controlling variables (chlorophyll a, apparent oxygen utilization (AOU), sea surface temperature, and sea surface salinity) further constrained the interplay of the processes driving the fCO2ssw distributions. Photosynthetic CO2 drawdown significantly offsets the influence of the upwelling of CO2-rich waters in the central Weddell gyre and enhanced the CO2 sink in the region. FCO2 of −6.9 mmol m–2 d–1 estimated for the Weddell gyre in this study was different from FCO2 of −2.5 mmol m–2 d–1 in autumn estimated in a previous study. Due to low CO2 data coverage during autumn, limited sea-air CO2 flux estimates from direct sea-surface CO2 observations particularly for the Weddell gyre region are available with which to compare the values estimated in this study. This highlights the importance of increasing seasonal CO2 observations especially during autumn/winter to improving the seasonal coverage of flux estimates in the seasonal sea ice-covered regions of the Southern Ocean.
Keywords: Sørishavet; karbondioksid; kjemi

The Weddell Gyre, Southern Ocean: Present Knowledge and Future Challenges - Vernet, M; Geibert, Walter; Hoppema, Mario; Brown, Peter J; Haas, Christian; Hellmer, Hartmut H; Jokat, Wilfried; Jullion, L; Mazloff, M; Bakker, D C E; Brearley, J A; Croot, Peter L; et al. (Reviews of Geophysics, 2019)
The Weddell Gyre (WG) is one of the main oceanographic features of the Southern Ocean south of the Antarctic Circumpolar Current which plays an influential role in global ocean circulation as well as gas exchange with the atmosphere. We review the state-of-the art knowledge concerning the WG from an interdisciplinary perspective, uncovering critical aspects needed to understand this system's role in shaping the future evolution of oceanic heat and carbon uptake over the next decades. The main limitations in our knowledge are related to the conditions in this extreme and remote environment, where the polar night, very low air temperatures, and presence of sea ice year-round hamper field and remotely sensed measurements. We highlight the importance of winter and under-ice conditions in the southern WG, the role that new technology will play to overcome present-day sampling limitations, the importance of the WG connectivity to the low-latitude oceans and atmosphere, and the expected intensification of the WG circulation as the westerly winds intensify. Greater international cooperation is needed to define key sampling locations that can be visited by any research vessel in the region. Existing transects sampled since the 1980s along the Prime Meridian and along an East-West section at ~62°S should be maintained with regularity to provide answers to the relevant questions. This approach will provide long-term data to determine trends and will improve representation of processes for regional, Antarctic-wide, and global modeling efforts—thereby enhancing predictions of the WG in global ocean circulation and climate.
Keywords: Sørishavet; Weddellhavet; biologi; brehylle; geologi; havis; havstrømmer; isbrem; isshelf; kjemi; oseanografi; sjøis; vannmasser; vannvirvler

On-site and in situ remediation technologies applicable to metal-contaminated sites in Antarctica and the Arctic: a review - Camenzuli, Danielle; Freidman, Benjamin L; Statham, Tom M; Mumford, Kathryn A; Gore, Damian B (Polar Research, 2013)
Effective management of contaminated land requires a sound understanding of site geology, chemistry and biology. This is particularly the case for Antarctica and the Arctic, which function using different legislative frame- works to those of industrialized, temperate environments and are logistically challenging environments to operate in. This paper reviews seven remediation technologies currently used, or demonstrating potential for on-site or in situ use at metal-contaminated sites in polar environments, namely permeable reactive barriers (PRB), chemical fixation, bioremediation, phytoremediation, electrokinetic separation, land capping, and pump and treat systems. The technologies reviewed are discussed in terms of their advantages, limitations and overall potential for the management of metal-contaminated sites in Antarctica and the Arctic. This review demonstrates that several of the reviewed technologies show potential for on-site or in situ usage in Antarctica and the Arctic. Of the reviewed technologies, chemical fixation and PRB are particularly promising technologies for metal-contaminated sites in polar environments. However, further research and relevant field trials are required before these technologies can be considered proven techniques. Keywords: Polar; heavy metals; remediation; contaminants; in situ
Keywords: Antarktis; biologi; forurensning; geologi; jord; kjemi; menneskelig påvirkning; polarområdene; tungmetaller

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Very little in situ produced radiocarbon retained in accumulating Antarctic ice - van der Kemp, Wybe J.M.; Alderliesten, Cees; van der Borg, Klaas; Holmlund, Per; de Jong, Arie F.M.; Karlöf, Lars; Lamers, R.A.N.; Oerlemans, Johannes; Thomassen, Martijn P.A.; van de Wal, Roderik S.W. (8th International Conference on Accelerator Mass Spectrometry, 2000)
Ice samples from Dronning Maud Land, Antarctica, were analyzed for 14CO2 and 14CO by accelerator mass spectrometry. Only a small amount (∼2%) of in situ produced radiocarbon was detected. The calibrated radiocarbon ages, corrected for in situ produced 14C, are in fair agreement with age estimates obtained from stratigraphical methods added to a gas inclusion model. The ages of the entrapped air range from recent to ca. 1200 AD.
Keywords: Dronning Maud Land; fysikk; karbondatering; karbondioksid; kjemi; massespektrometri